MANAGEMENT STRATEGY OF THE HALAL STUDIES CENTER AT MUHAMMADIYAH A.R. FACHRUDDIN UNIVERSITY (UNIMAR) IN ENHANCING HALAL LITERACY AWARENESS AMONG THE COMMUNITY OF TANGERANG REGENCY) - Wahyu Fajar Nugraha; Abu Naim; Nida Utami (RADJA PUBLIKA, 2025)
This study aims to analyze the management strategies employed by the Halal Study Center of Muhammadiyah A.R. Fachruddin University in enhancing halal literacy among communities in Tangerang Regency, Indonesia. In light of increasing public awareness regarding the halal status of consumable products, improving societal understanding of halal principles is a crucial step toward ensuring ethical and safe consumption. Utilizing a qualitative approach through interviews, observations, and document analysis, this research identifies key strategies, including community education programs, collaboration with governmental and religious institutions, support for halal certification processes among micro, small, and medium enterprises (MSMEs), and the use of digital media to broaden outreach. The findings reveal that these integrated efforts have significantly contributed to raising awareness and encouraging greater compliance with halal principles, particularly among local business actors. The study concludes that effective management, bolstered by strategic partnerships and community engagement, plays a vital role in developing a sustainable halal ecosystem